Balanced-detection raman induced kerr effect microscopy - Kumar, V; Casella, M; Molotokaite, E; Kukura, P; Manzoni, C; Polli, D; Marangoni, M; Cerullo, G (2012)
We introduce balanced-detection Raman-induced Kerr effect microscopy as a new powerful coherent Raman imaging technique, combining background-free detection with the absence of non-resonant background and linear dependence on sample concentration. © OSA 2012.